Clinical Trial Protocol: VAC060 Protocol v3.0 - Hill, A (University of Oxford, 2019)
This is a clinical trial protocol describing the VAC 060 study, undertaken by the Jenner Institute, sponsored by the University of Oxford. It was funded by a Strategic Primer grant award from the European and Developing Countries Clinical Trials Partnership (EDCTP) with co-funding from Swedish International Development Cooperation Agency (Sida); UK Medical Research Council; Irish Aid, Department of Foreign Affairs and Trade, Ireland;and Bundesministerium für Bildung und Forschung (BMBF), Germany and was performed by the Malaria Vectored Vaccines Consortium 2 (MVVC 2) (EDCTP, grant number SP.2011.41304.025). The European Vaccine Initiative (EVI) coordinated the EDCTP-funded MVVC 2 project. The work was also supported by the UK National Institute of Health Research through the Oxford Biomedical Research Centre (http://oxfordbrc.nihr.ac.uk/) (A91301 Adult Vaccine) and the Wellcome Trust (https://www. wellcome.ac.uk/) (084113/Z/07/Z).